Cross-border M&A: Challenges and opportunities in global business environment [Guest editors' introduction] - CAIZZA, Rosa (Institutional Knowledge at Singapore Management University, 2017)
Under a rapidly changing and globalizing environment, mergers and acquisitions (M&As) have become one of the most important strategic initiatives. In this context, cross-border M&As provide various opportunities and benefits such as expeditious entry into new markets by gaining local knowledge, supplier networks, government relationships, and customers embedded in the target firm.